Happy mapping as an alternative to overcome the problems in coconut genome mapping - C.K. Bandaranayake (International Coconut Community, 2004)
An excellent way of producing a reliable mapping population for quantitative trait loci analysis and marker assisted selection was considered. A physical mapping method known as ‘Happy Mapping’ was discussed to make a framework map as an alternative to overcome the problems associated with meiotic mapping.